Hubungan Dukungan Orang Tua Berbasis “Caring” dengan Pola Asuh Anak Balita - Rohmah, Nikmatur; Azza, Awatiful; Nugrahani, Ely Rahmatika (Jurnal Kesehatan, 2025)
Parental support is an important asset in raising toddlers. However, there are very few studies on "caring"-based parental support. The research aims to analyze the relationship between "caring"-based parental support and parenting patterns for toddlers—cross-sectional research design. The population is parents who have children under five in Jelbuk District, Jember Regency, East Java, Indonesia. The sample numbered 331 which were chosen randomly. The input variable is "caring" support which consists of trustworthy, respectful, empathetic, caring, and communicative. The outcome variable is parenting patterns for toddlers. Data were collected using a questionnaire technique, with the instrument being a structured questionnaire form. Data analysis uses logistic regression. The results of the study show that there is a relationship between parental support based on "caring" and parenting patterns for toddlers. Parents who care enough have a 3.46 times higher potential to provide good parenting compared to parents who care less (AOR 3.46; CI 95% 1.160-10.314). Parents who care a lot have 11,368 times higher potential to provide good parenting compared to parents who care less (AOR 11.368; CI 95% 3.411-37.883). Highly communicative parents have a 39.580 times higher potential for providing good parenting compared to less communicative parents (AOR 39.580; CI 95% 4.680-34.717). Caring and communicativeness are caring elements in parental support most related to child parenting. This study recommends a collaborative parenting program to improve parents' ability to build healthy communication and meaningful care for children under five.